The effect of normobaric hypoxia on acute exercise-induced changes in blood sphingoid base-1-phosphates metabolism in cyclists - Hodun, Katarzyna; Czuba, Miłosz; Płoszczyca, Kamila; Sadowski, Jerzy; Langfort, Józef; Chabowski, Adrian; Baranowski, Marcin (Biology of Sport, 2024)
Extracellularsphingosine-1-phosphate (S1P) emerged as an important regulator of muscle function. We previously found that plasma S1P concentration is elevated in response to acute exercise and training. Interestingly, hypoxia, which is commonly utilized in training programs, induces a similar effect. Therefore, the aim of the current study was to determine the effect of normobaric hypoxia on exercise-induced changes in blood sphingolipid metabolism. Fifteen male competitive cyclists performed a graded cycling exercise until exhaustion (GE) and a simulated 30 km individual time trial (TT) in either normoxic or hypoxic (FiO 2 = 16.5%) conditions. Blood samples were taken before the exercise, following its cessation, and after 30 min of recovery. We found that TT increased dihydrosphingosine-1-phosphate (dhS1P) concentration in plasma (both HDL- and albuminbound) and blood cells, as well as the rate of dhS1P release from erythrocytes, regardless of oxygen availability. Plasma concentration of S1P was, however, reduced during the recovery phase, and this trend was augmented by hypoxia. On the other hand, GE in normoxia induced a selective increase in HDL-bound S1P. This effect disappeared when the exercise was performed in hypoxia, and it was associated with reduced S1P level in platelets and erythrocytes. We conclude that submaximal exercise elevates total plasma dhS1P concentration via increased availability of dihydrosphingosine resulting in enhanced dhS1P synthesis and release by blood cells. Maximal exercise, on the other hand, induces a selective increase in HDL-bound S1P, which is a consequence of mechanisms not related to blood cells. We also conclude that hypoxia reduces post-exercise plasma S1P concentration.